kewirausahaan sosial INOVASI KEWIRAUSAHAAN SOSIAL DALAM MENANGANI KESULITAN DISTRIBUSI PRODUK AGROWISATA DI KOTA BATU - Garsione Agni Andrea; Sheidy Yudhiasta (Sekolah Tinggi Pariwisata Sahid Surakarta, 2022)
Social entrepreneurship is an entrepreneur who has the ability to solve problems in society to become business opportunities by making social changes including welfare and education and health, which are formed through collaboration between community organizations, other entrepreneurs, and stakeholders who have goals based on social values. During the Covid-19 pandemic, many problems occurred in the community, one of which was the manager of agro-tourism in Batu City. Agro-tourism in the form of picking apples and strawberries has difficulty in distributing its agro-tourism products in the form of fruit which ends up being thrown away. The method in this study uses a qualitative descriptive method by narrating statements in accordance with the results of the analysis of existing phenomena by exploration and classification. The social situation/sample is the manager of agro-tourism in Batu City which is managed independently by the local community using a random sampling method (probability sampling area). The results of this study present that the innovative idea of ​​social entrepreneurs helps to overcome the difficulties of agro-tourism managers in handling their products. This innovation can reduce the losses experienced by managers due to no tourist activity. The benefits of this innovation made by social entrepreneurs are not only felt by agro-tourism managers, but also to product recipient communities and volunteers in creating a sense of care for others and the environment.